Accounting and contracting choices around a change in fiduciary duties - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2017)
We exploit an influential 1991 Delaware court ruling to examine the impact of changes in managerial fiduciary duties on firms’ accounting and contracting choices. The ruling expanded directors’ fiduciary duties in favor of creditors and away from shareholders for a specific group of firms. Using a hand-collected sample of debt contracts around the ruling date, we find that, following the ruling, debt contracts of affected firms rely less on the use of income escalators (provisions in loan contracts which require changes in net worth to reflect losses in full, but only partially for gains and profits) and other conservative adjustments such as requiring net worth calculations to include extraordinary losses but not gains. In addition, affected firms exhibit lower abnormal accruals, more negative special items, and are more likely to adopt SFAS 106 using the immediate recognition method for OPEB liabilities. Our results hold across a battery of robustness tests. Overall, our study demonstrates how a shift in fiduciaries duties owed by management that enhances the relative power of creditors changes the nature of both financial reporting and debt contracting.